THE EFFECT OF TOBACCO SMOKING ON THE ORGANS AND TISSUES OF THE ORAL CAVITY - Karshieva Dilovar Rustamovna (Scholar Express Journals, 2023)
A person who smokes one pack of cigarettes a day makes more than 70,000 puffs a year, while the constituent components of tobacco smoke can affect the human body directly through the mucous membranes of the oral cavity, airways and respiratory sections of the lungs, as well as indirectly - being absorbed into the blood . At the same time, the organs and tissues of the oral cavity are the site of the primary contact of the smoker's body with the components of tobacco smoke. The resulting changes in the oral mucosa and minor salivary glands can be the first early symptoms for diagnosing diseases caused by smoking. The nature, mechanism of the damaging effect of tobacco smoke and the resulting changes in the oral mucosa, MSF and oral fluid in smokers are of theoretical and practical interest.
Keywords: Tobacco; oral cavity; sick children; leukoplakia